Strategic partnerships in the renewable energy sector in Portugal - Salavisa, I. (2018)
This paper focuses on the strategic partnerships established by firms operating in the renewable energy technologies sector in Portugal. The analysis aims at contributing to deepen the knowledge about the types and forms of partnerships in the renewables sector. The goal is to uncover the factors that explain the success of these partnerships and draw conclusions on the way they contributed to building a renewables cluster in Portugal.